China’s inauthentic UK Twitter diplomacy: a coordinated network amplifying PRC diplomats - Schliebs, M; Bailey, H; Bright, J; Howard, PN (Programme on Democracy and Technology, Oxford University, 2021)
Twitter accounts operated by diplomats, including that of the People's Republic of China (PRC), play an important role in the public diplomacy efforts of many governments. We audit all Twitter engagement with PRC diplomats stationed in the United Kingdom over an eight month period, from June 2020 to January 2021: - We identify a large network of Twitter accounts that demonstrate multiple forms of coordinated inauthentic activity. The network consists of 62 accounts in total, 29 of which were recently active until we flagged their activity for Twitter. Many accounts impersonate UK citizens, with biographies such as "political affairs commentator from London" and usernames such as @JenniferatUK, @UKJenniferin, or @GraceUK5. - This network has features and behaviors that demonstrate a coordinated information operation: - Account creation appears coordinated. Nearly a third of the accounts were created within minutes of each other and the vast majority only amplify and engage with the PRC's diplomats to the UK. - Account use appears coordinated. Many accounts sit dormant for extended periods and are activated together at chosen moments. Most parts of the network tend to be active for the morning and early evening hours when social media use in the UK is highest. - Account interaction appears coordinated. Many accounts focus exclusively on amplifying UK-based PRC diplomats, and do not engage with other PRC diplomats. Accounts in the network frequently amplify PRC diplomats within sixty seconds of a message from another account in the network. It appears that human operators manage some accounts. - Account messages use consistent phrases. Accounts in the network often replicate segments of speeches or commentary from the three most prominent Twitter accounts of the PRC representation in London. - This coordinated information operation drives a significant proportion of the engagement with the PRC's UK public diplomacy on Twitter. Over the eight month period, 44% of the ambassador's retweets and 20% of his replies came from the coordinated network. At several critical moments, as much as three-quarters of the engagement with the PRC's top diplomat in London came from this inauthentic public diplomacy network.